Electronic Measurement of a Clinical Quality Measure for Inpatient Hypoglycemic Events: A Multicenter Validation Study. Issue 10 (October 2020) - Santos, Carlos A.Q.; Conover, Craig; Shehab, Nadine; Geller, Andrew I.; Guerra, Yannis S.; Kramer, Holly; Kosacz, Nicole M.; Zhang, Huiyuan; Budnitz, Daniel S.; Trick, William E.
Abstract : Background: Hypoglycemia related to antidiabetic drugs (ADDs) is important iatrogenic harm in hospitalized patients. Electronic identification of ADD-related hypoglycemia may be an efficient, reliable method to inform quality improvement. Objective: Develop electronic queries of electronic health records for facility-wide and unit-specific inpatient hypoglycemia event rates and validate query findings with manual chart review. Methods: Electronic queries were created to associate blood glucose (BG) values with ADD administration and inpatient location in 3 tertiary care hospitals with Patient-Centered Outcomes Research Network (PCORnet) databases. Queries were based on National Quality Forum criteria with hypoglycemia thresholds <40 and <54 mg/dL, and validated using a stratified random sample of 321 BG events. Sensitivity and specificity were calculated with manual chart review as the reference standard. Results: The sensitivity and specificity of queries for hypoglycemia events were 97.3% [95% confidence interval (CI), 90.5%–99.7%] and 100.0% (95% CI, 92.6%–100.0%), respectively for BG <40 mg/dL, and 97.7% (95% CI, 93.3%–99.5%) and 100.0% (95% CI, 95.3%–100.0%), respectively for <54 mg/dL. The sensitivity and specificity of the query for identifying ADD days were 91.8% (95% CI, 89.2%–94.0%) and 99.0% (95% CI, 97.5%–99.7%). Of 48 events missed by the queries, 37 (77.1%) were due to incomplete identification of insulin administered by infusion. Facility-wide hypoglycemia rates were 0.4%–0.8% (BG <40 mg/dL) and 1.9%–3.0% (BG <54 mg/dL); rates varied by patient care unit. Conclusions: Electronic queries can accurately identify inpatient hypoglycemia. Implementation in non–PCORnet-participating facilities should be assessed, with particular attention to patient location and insulin infusions. Abstract : Supplemental Digital Content is available in the text.